1993
DOI: 10.1111/j.1476-5381.1993.tb13821.x
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of the NK1 receptor antagonist CP‐96,345 with L‐type calcium channels and its functional consequences

Abstract: 1 We investigated the effects of the non-peptide NK1 receptor antagonist, CP-96,345, its inactive enantiomer CP-96,344, and the racemic mixture ( ± )-CP-96,345, on the binding of [3H]-nimodipine and [3H]-diltiazem to L-type calcium channels in rat cerebral cortex membranes. In isolated peripheral tissues containing tachykinin receptors, the effects of (± )-CP-96,345 have been compared with those of diltiazem.2 In guinea-pig trachea, (± )-CP-96,345 produced antagonism of responses to the selective NK, agonists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(35 citation statements)
references
References 26 publications
1
34
0
Order By: Relevance
“…The advent of nonpeptide antagonists (Snider et al, 1991) allowed a more detailed examination of binding characteristics. Despite this, early compounds such as the NK1 antagonist CP-96,345 used by Huber et al (1993a,b) were later found to have confounding effects, including a strong affinity to block the L-type Ca 2ϩ channel (Guard et al, 1993). As such, in the present study, we have extended the pioneering observations by Huber et al (Huber et al, 1993a,b) by using a newer generation of selective receptor antagonists (Holzer and Holzer-Petsche, 1997a).…”
Section: Discussionsupporting
confidence: 63%
“…The advent of nonpeptide antagonists (Snider et al, 1991) allowed a more detailed examination of binding characteristics. Despite this, early compounds such as the NK1 antagonist CP-96,345 used by Huber et al (1993a,b) were later found to have confounding effects, including a strong affinity to block the L-type Ca 2ϩ channel (Guard et al, 1993). As such, in the present study, we have extended the pioneering observations by Huber et al (Huber et al, 1993a,b) by using a newer generation of selective receptor antagonists (Holzer and Holzer-Petsche, 1997a).…”
Section: Discussionsupporting
confidence: 63%
“…Several non-peptide NK, receptor antagonists, for example CP-96,345 and RP67580, have affinity for Na' and L-type Ca2+ channels (Schmidt et al, 1992;Caeser et al, 1993;Guard et al, 1993;Constantine et al, 1994;Wang et al, 1994). However, GR203040 was found to have only a weak effect on ion channels.…”
Section: Discussionmentioning
confidence: 99%
“…Several high affinity peptide antagonists, such as spantide II Hakanson et al, 1990; and FK 888 (Fujii et al, 1992;Hirayama et al, 1993), have also recently been described. However, non-peptide antagonists have been found to possess effects not related to tachykinin receptor antagonism (Lecci et al, 1991;Nagahisa et al, 1992;Schmidt et al, 1992;Wang & Hikanson, 1992a;Guard et al, 1993;Tamura et al, 1993), including non-specific effects on neurotransmission (Wang & HAkanson, 1992a;Wang et al, 1994) and local anaesthetic-like actions (Caeser et al, 1993;Tamura et al, 1993;Wang et al, 1994). The concentrations needed to exert these non-specific actions are approximately 10 times higher than those needed to produce blockade of tachykinin receptors (Wang & Hakanson, 1992a;Wang et al, 1994).…”
Section: Introduction Methodsmentioning
confidence: 99%